A thromboplastic hydrogel wound dressing and methods of making and using the same

CN118045222BActive Publication Date: 2026-10-23EAST CHINA UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410164928.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-02-05
Publication Date
2026-10-23
Estimated Expiration
2044-02-05

AI Technical Summary

Technical Problem

[0004]本发明的目的是提供一种促凝血的水凝胶伤口敷料及其制备方法和应用,从而解决现有的伤口敷料无法较好地促进凝血、并且无法进行伤口监测、需要多次更换敷料进而给患者带来不必要的痛苦的问题

Benefits of technology

[0020]根据本发明提供的一种促凝血的水凝胶伤口敷料及其制备方法和应用,相对于现有技术的优越性在于:1)该伤口敷料具有双层结构,既有一定的结构强度,又保留了良好的粘附性,其中,PVA1799水凝胶层具有较好的结构强度且在90℃以下几乎不溶于水,起到保护层的作用,PVA2088水凝胶层黏附性能较好,起到黏附层或载药层的作用;2)通过在PVA2088水凝胶层中掺入碳酸钙,当伤口感染细菌时通过pH变化(感染伤口pH值通常为5~6.5)诱导释放钙离子,促进凝血过程;3)当加入碳酸钙为0~0.2wt%时,特别是0~0.05wt%时,该伤口敷料透明性良好,方便进行伤口监测,避免多次更换敷料给患处造成二次伤害。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118045222B_ABST
    Figure CN118045222B_ABST
Patent Text Reader

Abstract

The application provides a blood coagulation promoting hydrogel wound dressing and a preparation method and application thereof, and the preparation method comprises the following steps: S1: PVA2088 is added into deionized water to prepare a 5%-15% PVA2088 multi-bubble solution, and calcium carbonate is added, and the concentration of the calcium carbonate is 0-0.2 wt%; S2: an appropriate amount of the PVA2088 multi-bubble solution is taken in a container, and is subjected to freezing, vacuumizing and drying to prepare a PVA2088 hydrogel layer; S3: PVA1799 is dissolved in deionized water to prepare a 5%-10% PVA1799 solution; and S4: an appropriate amount of the PVA1799 solution is cast on the PVA2088 hydrogel layer, vacuumizing and drying are performed, and the hydrogel wound dressing is obtained. The hydrogel wound dressing prepared according to the application has the advantages of high structural strength, good adhesion, blood coagulation promotion, high transparency and the like, can be used for wound monitoring, and has a good application prospect in the field of skin tissue repair and regeneration.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of wound repair, particularly to the field of skin tissue repair and regeneration, and specifically to a procoagulant hydrogel wound dressing, its preparation method, and its application. Background Technology

[0002] Hydrogels are three-dimensional hydrophilic polymer matrices with high water absorption capacity. Their three-dimensional network structure gives them tissue-like elasticity, allowing them to bind well to skin tissue and reduce pain. High water content helps maintain a moist environment, promoting faster wound healing. Polyvinyl alcohol (PVA), as a widely studied material in hydrogel wound dressings, possesses hydrophilicity, biocompatibility, biodegradability, chemical resistance, good adhesion, non-toxicity, and high mechanical properties, creating favorable conditions for wound healing. Typical wound healing generally involves four steps: hemostasis, inflammation, proliferation, and remodeling. Major hemorrhage still accounts for 40% of post-traumatic mortality, and reducing post-traumatic blood loss to prevent related complications has driven the rapid development of hemostatic dressings. Coagulation is a complex process in which plasma transforms from unstable platelet plugs into stable and insoluble fibrin, representing a multifaceted response of the body to bleeding.

[0003] However, traditional dressings are not effective at promoting blood clotting. Furthermore, frequent dressing changes are necessary to monitor wound healing, which can easily cause secondary injury and increase patient suffering. Therefore, it is necessary to develop a hydrogel wound dressing with good transparency for easy wound monitoring while also promoting blood clotting. Summary of the Invention

[0004] The purpose of this invention is to provide a hydrogel wound dressing that promotes blood clotting, its preparation method, and its application, thereby solving the problems that existing wound dressings cannot effectively promote blood clotting, cannot be used for wound monitoring, and require frequent dressing changes, thus causing unnecessary pain to patients.

[0005] To solve the above-mentioned technical problems, the present invention adopts the following technical solution:

[0006] According to a first aspect of the present invention, a method for preparing a procoagulant hydrogel wound dressing is provided, comprising the following steps: S1: PVA2088 is added to deionized water to prepare a 5% to 15% PVA2088 multifoam solution, and calcium carbonate is added, wherein the concentration of calcium carbonate is 0 to 0.2 wt%; S2: An appropriate amount of PVA2088 multifoam solution is placed in a container, vacuumed to remove internal air bubbles, dried in an oven, and air-dried at room temperature to obtain a PVA2088 hydrogel layer; S3: PVA1799 is dissolved in deionized water to prepare a 5% to 10% PVA1799 solution; S4: An appropriate amount of PVA1799 solution is poured onto the dried PVA2088 hydrogel layer obtained in step S2, vacuumed, dried in an oven, and air-dried at room temperature to finally obtain a hydrogel wound dressing composed of a PVA2088 hydrogel layer and a PVA1799 hydrogel layer.

[0007] Preferably, step S1 includes: adding a small amount of PVA2088 to deionized water to prepare a 0.5% to 2% PVA2088 solution, then adding calcium carbonate, and then adding the remaining PVA2088 to mix and prepare a 5% to 15% PVA2088 multi-bubble solution.

[0008] Preferably, in step S1, the concentration of calcium carbonate in the PVA2088 multifoam solution is 0-0.2 wt%, more preferably 0-0.05 wt%, and most preferably 0.05 wt%. Within this preferred range, the PVA2088 hydrogel layer can better ensure a certain degree of transparency while also having good procoagulant function.

[0009] Preferably, in step S1, the calcium carbonate used has a particle size of 50-150 nm, more preferably 100 nm.

[0010] Preferably, step S2 includes: drying in an oven at 50-60°C for 4-6 hours, and then air-drying at room temperature for 48-72 hours.

[0011] Preferably, step S3 includes: adding PVA1799 to deionized water at 90-96°C to prepare a 5%-10% PVA1799 solution.

[0012] Preferably, step S4 includes: evacuating the vacuum pump for 1-2 hours, drying in a 50°C oven for 2-4 hours, and then air-drying at room temperature for 24-48 hours.

[0013] According to a second aspect of the present invention, a procoagulant hydrogel wound dressing prepared according to the above-described preparation method is provided. The bilayer hydrogel is a bilayer hydrogel composed of a PVA2088 hydrogel layer and a PVA1799 hydrogel layer. The PVA2088 hydrogel layer is prepared by dissolving calcium carbonate-doped PVA2088 in deionized water, with the calcium carbonate doping amount being 0–0.02% wt. The PVA1799 hydrogel layer is prepared by dissolving PVA1799 in deionized water. The PVA2088 hydrogel layer serves as an adhesive layer, and the PVA1799 hydrogel layer serves as a solvent-resistant protective layer.

[0014] According to a preferred embodiment of the present invention, the thickness of the PVA2088 hydrogel layer is 0.55 to 0.65 mm, and the thickness of the PVA1799 hydrogel layer is 0.06 to 0.1 mm.

[0015] According to the research of this invention, when the thickness of the PVA2088 hydrogel layer is 0.55 to 0.65 mm, the wound dressing can be guaranteed to have sufficient adhesion, approximately 10,000 to 12,000 Pa. When the thickness of the PVA1799 hydrogel layer is 0.06 to 0.1 mm, a relatively smooth solvent-resistant protective layer can be formed. If the thickness of the PVA1799 layer is further increased, the film thickness will be extremely uneven because the PVA1799 layer is very easy to shrink during the drying process.

[0016] According to a third aspect of the present invention, a procoagulant hydrogel wound dressing is provided for use in skin tissue repair and regeneration.

[0017] It should be understood that current polyvinyl alcohol-based dressings mainly use polyvinyl alcohol with a degree of hydrolysis of 99% blended with other biocompatible materials (such as alginate, chitosan, etc.), and form films through electrospinning and other processes. This process is complex, resulting in low adhesion or difficulty in controlling transparency, and it can only achieve hemostasis through physical barrier, failing to promote the coagulation process. To improve the aforementioned defects of existing dressings, the range of materials that can be selected is greatly limited. However, this invention is surprisingly effective. By preparing a bilayer film using PVA1799 with a degree of hydrolysis of 99% and PVA2088 with a degree of hydrolysis of 88%, it not only possesses excellent transparency but also ensures a certain degree of adhesion and structural strength. Furthermore, to achieve targeted promotion of coagulation, this invention introduces 0-0.2 wt% calcium carbonate to impart coagulation-promoting function, while the material still maintains good transparency. When a wound is infected by bacteria, the pH value drops from 7.4 to 5-6.5. In this weakly acidic environment, calcium carbonate will partially decompose and release calcium ions, which participate in and promote the coagulation process.

[0018] It should be understood that Ca 2+As the only ionic coagulation factor, it plays a crucial role in catalyzing the formation of coagulation factor X and fibrin fixation. During coagulation, fibrinogen is enzymatically broken down into fibrin monomers by thrombin. Fibrin monomers in Ca... 2+ With the participation of activating factors, cross-linking occurs, forming a fibrin network. Finally, platelets are adsorbed and activated on the fibrin network, forming fibrin clots and enhancing the hemostatic effect of platelets. Wounds are highly susceptible to bacterial infection during the healing process. Due to the accumulation of bacterial byproducts (such as lactic acid), the wound pH is typically between 5 and 6.5. Calcium carbonate has good biocompatibility, is difficult to dissolve in water, but can partially decompose in a weakly acidic environment, releasing calcium ions. Therefore, this invention introduces nano-calcium carbonate into wound dressings, inducing the release of calcium ions in the wound environment, which then participate in the coagulation process.

[0019] Secondly, as is generally known in the art, PVA2088 easily generates a large number of bubbles during dissolution, which are usually removed by adding defoaming agents (such as organosilicon or polyether). However, this defoaming method not only introduces new impurities, which is detrimental to wound treatment, but also reduces the transparency of the film after formation due to the color of the defoaming agent itself. However, the present invention uses a cryogenic vacuum method, which can effectively remove bubbles from the PVA2088 solution, and only requires about 6 to 7 hours, which is significantly shorter than direct vacuuming (18 to 24 hours).

[0020] The advantages of the procoagulant hydrogel wound dressing, its preparation method, and its application provided by the present invention compared with the prior art are as follows: 1) The wound dressing has a double-layer structure, which has both structural strength and good adhesion. The PVA1799 hydrogel layer has good structural strength and is almost insoluble in water below 90°C, thus acting as a protective layer. The PVA2088 hydrogel layer has good adhesion properties, thus acting as an adhesive layer or drug-carrying layer; 2) By incorporating calcium carbonate into the PVA2088 hydrogel layer, when the wound is infected with bacteria, the release of calcium ions is induced by pH changes (the pH value of infected wounds is usually 5-6.5), thus promoting the coagulation process; 3) When the amount of calcium carbonate added is 0-0.2 wt%, especially 0-0.05 wt%, the wound dressing has good transparency, which facilitates wound monitoring and avoids secondary damage to the affected area caused by repeated dressing changes.

[0021] In summary, according to the present invention, a hydrogel wound dressing is provided that simultaneously possesses high structural strength and good adhesion, has a procoagulant function, high transparency, allows for wound monitoring, and avoids secondary damage caused by repeated dressing changes. Attached Figure Description

[0022] Figure 1The preparation process of the PVA2088 hydrogel layer in Example 1 is shown, wherein (a) the PVA2088 multi-bubble solution is degassed; (b) it is frozen at -18°C for 1 hour; (c) it is vacuumed for 2 hours and then thawed at the bottom by heating to 99°C with an induction cooker; and (d) it is vacuumed again at room temperature for 3 hours.

[0023] Figure 2 The effects of different PVA1799 addition amounts on the formation of bilayer hydrogel films are shown in Example 1; wherein the amounts of PVA1799 solution used are (a) 10 mL; (b) 20 mL; (c) 30 mL;

[0024] Figure 3 The diagram shows the swelling of the PVA bilayer film in Example 2; where (a) before immersion; (b) after immersion for 3 hours; (c) after immersion for 12 hours; and (d) after immersion for 24 hours.

[0025] Figure 4 The swelling curve of the PVA bilayer film prepared in Example 2 is shown;

[0026] Figure 5 The following are comparative images of the surface morphology of the PVA2088 hydrogel layer in Example 3: (a) and (b) are the surface morphology of the PVA2088 hydrogel layer without calcium carbonate doping; (c) and (d) are the surface morphology of the PVA2088 hydrogel layer with 0.05 wt% calcium carbonate doping.

[0027] Figure 6 The EDS energy spectrum of the PVA2088 hydrogel layer in Example 3 is shown; wherein, (a) is the EDS energy spectrum of PVA2088 without calcium carbonate doping; and (b) is the EDS energy spectrum of PVA2088 with 0.05wt% calcium carbonate doping.

[0028] Figure 7 The results of Example 4 show the Ca2+ of the 0.05 wt% calcium carbonate-doped PVA bilayer film at different pH values. 2+ Ion release curve;

[0029] Figure 8 The following are examples of PVA bilayer films with different calcium carbonate doping contents in Example 5: the PVA1799 layer has a thickness of approximately 0.08 mm, and the PVA2088 layer has a thickness of approximately 0.6 mm; wherein, (a) 0 wt%; (b) 0.05 wt%; (c) 0.1 wt%; (d) 0.2 wt%.

[0030] Figure 9 The following are tensile specimens of the PVA bilayer film in Example 5: (a) Dimensions of the tensile specimens; (b) 0 wt%, 0.05 wt%, 0.1 wt%, and 0.2 wt% calcium carbonate doped specimens from left to right.

[0031] Figure 10 The tensile tests of PVA bilayer films with different calcium carbonate doping contents are shown in Example 5;

[0032] Figure 11 The adhesion test method for PVA2088 doped with different amounts of calcium carbonate in Example 6 is shown;

[0033] Figure 12 The adhesion test of PVA bilayer films with different calcium carbonate doping contents is shown in Example 6;

[0034] Figure 13 The image shown is a SEM image of the PVA bilayer membrane after a protein solution was dropped onto it in Example 7.

[0035] Figure 14 The SEM image shown is of a 0.05% CaCO3-doped PVA bilayer film after a protein solution was dropped onto it in Example 8.

[0036] Figure 15 The SEM image of the 0.1% CaCO3-doped PVA bilayer membrane after being dropped into the protein solution in Example 9 is shown.

[0037] Figure 16 The SEM image of the 0.2% wt CaCO3-doped PVA bilayer membrane after being dropped into the protein solution in Example 10 is shown.

[0038] Figure 17 The image shown is a SEM image of the PVA bilayer membrane after being dropped into the platelet solution in Example 11.

[0039] Figure 18 The SEM image of the 0.05% wt CaCO3-doped PVA bilayer membrane after being dropped into the platelet solution in Example 12 is shown.

[0040] Figure 19 The SEM image of the 0.1% wt CaCO3-doped PVA bilayer membrane after being dropped into the platelet solution in Example 13 is shown.

[0041] Figure 20 The SEM image of the 0.2% wt CaCO3-doped PVA bilayer membrane in Example 14 after being dropped into the platelet solution is shown.

[0042] Figure 21 The image shown is a SEM image of the platelet solution after incubation of protein with a PVA bilayer membrane in Example 15.

[0043] Figure 22 The image shown is a SEM image of the protein incubated with a 0.05% wt CaCO3-doped PVA bilayer membrane in Example 16, followed by the addition of platelet solution.

[0044] Figure 23The image shown is a SEM image of the protein incubated with a 0.1% wt CaCO3-doped PVA bilayer membrane in Example 17, followed by the addition of platelet solution.

[0045] Figure 24 The image shown is a SEM image of the protein after incubation with a 0.2 wt% CaCO3-doped PVA bilayer membrane in Example 18, followed by the addition of a platelet solution. Detailed Implementation

[0046] The present invention will be further described below with reference to specific embodiments. It should be understood that the following embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Unless otherwise specified, the techniques used in the embodiments are conventional practices in the art, or experimental methods recommended by the reagent kit and instrument manufacturers. Unless otherwise specified, the reagents and materials used in the embodiments are commercially available.

[0047] Table 1. Chemical reagents used in some of these embodiments.

[0048] Example 1

[0049] A hydrogel wound dressing for promoting hemostasis was prepared by means of the following steps: 1) 0-0.2 wt% of 100 nm calcium carbonate was added to a 0.5%–2% PVA2088 solution to mix the calcium carbonate evenly at a low viscosity, and then PVA2088 was added to the solution to prepare a 5%–15% PVA2088 multi-bubble solution; 2) 20 g of the multi-bubble solution was placed in a petri dish and covered with an iron ring to increase the wall height. Internal air bubbles were removed by freezing and vacuuming. After drying in a 50°C oven for 5 hours, the solution was air-dried at room temperature (25°C) for 48–72 hours to obtain a PVA2088 monolayer film (e.g., ...). Figure 1 (as shown); 3) Add an appropriate amount of PVA1799 to deionized water at 96℃ and dissolve for 1.5h to prepare PVA1799 solutions with concentrations of 5% to 10%; 4) Take 10mL, 20mL, and 30mL of PVA1799 solution respectively and pour them onto the dried PVA2088 monolayer membrane in a petri dish. Vacuum the membrane in a vacuum pump for 1h, then dry it in a 50℃ oven for 3h. After drying, air dry it at room temperature (25℃) for 24 to 48h to obtain a PVA double-layer membrane (as shown); Figure 2 (As shown). In this double-layer film, the adhesive layer PVA2088 has a thickness of 0.55–0.65 mm to ensure sufficient adhesion (10000–12000 Pa), and the PVA1799 layer has a thickness of 0.06–0.1 mm (as shown). Figure 2As shown in a), a relatively smooth, solvent-resistant protective layer is formed. If the thickness of the PVA1799 layer is further increased, the film thickness will be extremely uneven due to the easy shrinkage of the PVA1799 layer during the drying process (as shown in a diagram). Figure 2 (as shown in b and c).

[0050] Example 2

[0051] A bilayer film was prepared using PVA1799 and PVA2088, with the PVA1799 layer approximately 0.08 mm thick and the PVA2088 layer approximately 0.6 mm thick. The PVA bilayer film was cut into 20 × 20 mm pieces and placed in a 200 mL beaker. 100 mL of deionized water was added to the beaker. The mass of the hydrogel was recorded every half hour and analyzed using the formula: The swelling ratio was calculated, where W0 is the initial mass and W1 is the mass after immersion. Three parallel samples were designed. The PVA bilayer film reached a swelling ratio of 250% within 3 hours. At this point, the hydrogel film maintained its shape and good transparency. Figure 3 After 6 hours, the swelling level stabilized and almost stopped, with a final swelling rate of 400%. Figure 4 ).

[0052] Example 3

[0053] 0.05 wt% 100 nm calcium carbonate was added to a PVA2088 solution, and the surface morphology of the PVA2088 film and the PVA2088 film doped with 0.05 wt% calcium carbonate were observed using a field emission scanning electron microscope (SEM-4800). The observations were made at a voltage around 3.7 keV. Figure 6 ), in samples without calcium carbonate doping (such as Figure 6 As shown in a), no calcium absorption peak is generated in the sample, while the sample doped with calcium carbonate (such as...) Figure 6 As shown in b), there is a distinct calcium absorption peak, indicating that there are particulate embedded particles (such as calcium carbonate) on the surface of the 0.05 wt% calcium carbonate PVA2088 film. Figure 5 (See c in the image) represents nano-doped calcium carbonate. The calcium carbonate particles are well dispersed in PVA2088, with the surface calcium carbonate mostly embedded in the surface layer. Although a small amount of calcium carbonate particles still agglomerate, almost all are within the 1 μm scale (e.g., ...). Figure 5 (as shown in d).

[0054] Example 4

[0055] 0.05wt% 50nm calcium carbonate was added to a PVA2088 solution, and then PVA1799 and PVA2088 were used to prepare a bilayer film, with the PVA1799 layer approximately 0.08mm thick and the PVA2088 layer approximately 0.6mm thick. Five groups of PBS solutions with different pH values ​​(pH 4, 5, 6.5, 7.4, and 8.5) were prepared. Five (20*20mm) 0.05wt% calcium carbonate-doped PVA bilayer films were added to five 50mL centrifuge tubes. The solution was changed at 1h, 2h, 3h, 6h, 12h, 24h, and 48h, with 10mL of PBS solution added to the centrifuge tube each time, and the solution was collected after each soaking. The PVA bilayer film completed the ion release process within 12h. When the pH dropped to between 5.0 and 6.5 (simulating the pH drop caused by bacterial infection in a wound), CaCO3 partially decomposed, and Ca... 2+ The release rate reaches 45-54 mg / L, which can participate in subsequent coagulation processes (such as... Figure 7 (As shown).

[0056] Example 5

[0057] 0 wt%, 0.05 wt%, 0.1 wt%, and 0.2 wt% 150 nm calcium carbonate were added to a PVA2088 solution, respectively. Then, bilayer films of PVA1799 and PVA2088 were prepared, with the PVA1799 layer approximately 0.08 mm thick and the PVA2088 layer approximately 0.6 mm thick. Photographs of PVA bilayer films with different calcium carbonate doping contents are shown below. Figure 8 As shown. From Figure 8 As can be seen, a calcium carbonate doping concentration of 0.05 wt% best ensures the transparency of the bilayer film. Subsequently, the mechanical properties of the PVA bilayer film were tested using a small tensile testing machine. Dumbbell-shaped specimens were cut (…). Figure 9 The tensile strength of the PVA bilayer film without calcium carbonate was 35*2*0.65 (gauge length 10cm, initial test length 20cm), and the tensile rate was 0.1mm / s. The tensile strength of the PVA bilayer film without calcium carbonate was lower than that of the other groups of PVA bilayer films with calcium carbonate. When the calcium carbonate content was 0-0.2wt%, the tensile stress increased with increasing calcium carbonate content. All groups of films exhibited good mechanical properties. Without calcium carbonate, the tensile stress was 33-45 MPa. With 0.2wt% calcium carbonate, the tensile strength was the highest, with a tensile stress of 44-52 MPa. Figure 10 ).

[0058] Example 6

[0059] 0 wt%, 0.05 wt%, 0.1 wt%, and 0.2 wt% 100 nm calcium carbonate were added to a PVA2088 solution. A bilayer film of PVA1799 and PVA2088 was then prepared, with the PVA1799 layer approximately 0.08 mm thick and the PVA2088 layer approximately 0.6 mm thick. The PVA bilayer film was cut to 20 × 20 mm dimensions. The PVA1799 side was adhered to a plastic sheet using 502 glue and soaked in deionized water for 0.5 h. Then, the hydrogel (PVA2088 side) was adhered to pigskin, and the tissue adhesion strength was measured. Figure 11 The ratio of maximum peel load to bonded area was used to measure bond strength. There was no significant difference in bond strength among the calcium carbonate-doped samples in each group. Figure 12 The bonding strength reaches 10,000 to 12,000 Pa.

[0060] Example 7

[0061] A single-layer PVA 2088 membrane was prepared, and then PVA 1799 was cast onto it to form a PVA bilayer film. The PVA 1799 layer was 0.06 mm thick, and the PVA 2088 layer was 0.55 mm thick. The PVA bilayer membrane (10 × 10 mm) was placed in a 24-well plate with the PVA 2088 side facing upwards. 20 μL of 50 mg / L porcine protein solution was slowly added dropwise to the PVA bilayer membrane, and then the plate was incubated in a constant temperature incubator for 1 hour. 20 μL of deionized water was then slowly added dropwise to the 50 mg / L protein solution incubator, and after wetting for 1 minute, the deionized water was gently wiped away with absorbent paper. After standing for 0.5 h, 20 μL of 2% PTA solution was slowly added dropwise to the area where 50 mg / L protein solution was added. After incubation at a constant temperature for 0.5 h, 20 μL of deionized water was slowly added dropwise to the area where PBS or 50 mg / L protein solution was added. After wetting for 1 min, the deionized water was gently wiped off with absorbent paper. After standing for 48 h, the membrane in the area where protein solution was added was cut, platinum-coated, and SEM images were taken. No obvious fibrin network was formed on the PVA bilayer membrane without calcium carbonate doping. Figure 13 ).

[0062] Example 8

[0063] 0.05% wt 100 nm CaCO3 was added to the PVA2088 solution, and then a bilayer film was prepared using PVA1799 and CaCO3-introduced PVA2088, with the PVA1799 layer having a thickness of 0.1 mm and the PVA2088 layer having a thickness of 0.65 mm. The PVA bilayer film (10 × 10 mm) was placed in a 24-well plate with the PVA2088 side facing upwards. 20 μL of 50 mg / L porcine protein solution was slowly added dropwise to the PVA bilayer film, and then the plate was incubated in a constant temperature incubator for 1 h. 20 μL of deionized water was slowly added dropwise to the 50 mg / L protein solution incubator, and after wetting for 1 min, the deionized water was gently wiped away with absorbent paper. After standing for 0.5 h, 20 μL of 2% PTA solution was slowly added dropwise to the area where 50 mg / L protein solution was added. After incubation at a constant temperature for 0.5 h, 20 μL of deionized water was slowly added dropwise to the area where PBS or 50 mg / L protein solution was added. After wetting for 1 min, the deionized water was gently wiped off with absorbent paper. After standing for 48 h, the membrane in the area where protein solution was added was cut, platinum-coated, and SEM images were taken. No significant fibrin network formation was observed on the PVA bilayer membrane doped with 0.05 wt% calcium carbonate. Figure 14 ).

[0064] Example 9

[0065] 0.1% wt 100nm CaCO3 was added to the PVA2088 solution, and then a bilayer film was prepared using PVA1799 and CaCO3-introduced PVA2088, with the PVA1799 layer approximately 0.08 mm thick and the PVA2088 layer approximately 0.6 mm thick. The PVA bilayer film (10 × 10 mm) was placed in a 24-well plate with the PVA2088 side facing upwards. 20 μL of 50 mg / L porcine protein solution was slowly added dropwise to the PVA bilayer film, and then the plate was incubated in a constant temperature incubator for 1 h. 20 μL of deionized water was slowly added dropwise to the 50 mg / L protein solution incubator, and after wetting for 1 min, the deionized water was gently wiped away with absorbent paper. After standing for 0.5 h, 20 μL of 2% PTA solution was slowly added dropwise to the area where 50 mg / L protein solution was added. After incubation at a constant temperature for 0.5 h, 20 μL of deionized water was slowly added dropwise to the area where PBS or 50 mg / L protein solution was added. After wetting for 1 min, the deionized water was gently wiped off with absorbent paper. After standing for 48 h, the membrane in the area where protein solution was added was cut, platinum-coated, and SEM images were taken. A relatively obvious fibrin network was formed on the PVA bilayer membrane doped with 0.1% calcium carbonate. Figure 15 ).

[0066] Example 10

[0067] 0.2% wt 100nm CaCO3 was added to the PVA2088 solution, and then a bilayer film was prepared using PVA1799 and CaCO3-introduced PVA2088, with the PVA1799 layer approximately 0.08 mm thick and the PVA2088 layer approximately 0.6 mm thick. The PVA bilayer film (10 × 10 mm) was placed in a 24-well plate with the PVA2088 side facing upwards. 20 μL of 50 mg / L porcine protein solution was slowly added dropwise to the PVA bilayer film, and then the plate was incubated in a constant temperature incubator for 1 h. 20 μL of deionized water was slowly added dropwise to the 50 mg / L protein solution incubator, and after wetting for 1 min, the deionized water was gently wiped away with absorbent paper. After standing for 0.5 h, 20 μL of 2% PTA solution was slowly added dropwise to the area where 50 mg / L protein solution was added. After incubation at a constant temperature for 0.5 h, 20 μL of deionized water was slowly added dropwise to the area where PBS or 50 mg / L protein solution was added. After wetting for 1 min, the deionized water was gently wiped off with absorbent paper. After standing for 48 h, the membrane in the area where protein solution was added was cut, platinum-coated, and SEM images were taken. A thicker fibrin network layer was formed on the PVA bilayer membrane doped with 0.2 wt% calcium carbonate, indicating that Ca... 2+ Increased ion content promotes the conversion of fibrinogen to fibrin. Figure 16 ).

[0068] Example 11

[0069] A PVA2088 monolayer was prepared, and then PVA1799 was cast on top to form a PVA bilayer film, with the PVA1799 layer approximately 0.08 mm thick and the PVA2088 layer approximately 0.6 mm thick. The PVA bilayer film (10 × 10 mm) was placed in a 24-well plate with the PVA2088 side facing upwards. 50 μL (33 mg / L) of platelet solution was slowly added dropwise to the PVA bilayer film, and the plate was incubated for 1.5 h. 50 μL of deionized water was then slowly added dropwise to the platelet solution area of ​​the sample, and after wetting for 1 min, the deionized water was gently wiped off with absorbent paper. After standing for 48 h, the area of ​​the film with the platelet solution added was cut, platinum-coated, and SEM images were taken. In samples where platelet solution was directly added to the surface of the PVA bilayer film, a thin fibrin network layer appeared. Figure 17 This also indicates that the PVA bilayer membrane has good biocompatibility.

[0070] Example 12

[0071] 0.05% wt 100nm CaCO3 was added to PVA2088 solution, and then a bilayer film was prepared using PVA1799 and PVA2088 with CaCO3 incorporation. The PVA1799 layer was approximately 0.08 mm thick, and the PVA2088 layer was approximately 0.6 mm thick. 50 μL (33 mg / L) platelet solution was slowly dropped into the PVA bilayer film, and the film was incubated in a constant temperature incubator for 1.5 h. 50 μL of deionized water was slowly dropped into the platelet solution area of ​​the sample, and after wetting for 1 min, the deionized water was gently wiped off with absorbent paper. After standing for 48 h, the area of ​​the film with the platelet solution was cut, platinum-coated, and SEM images were taken. After directly dropping the platelet solution onto the film surface, a thinner fibrin network layer appeared, which was more dense than that of the sample without calcium carbonate doping. Figure 18 ).

[0072] Example 13

[0073] 0.1% wt 100nm CaCO3 was added to a PVA2088 solution, and then a bilayer film was prepared using PVA1799 and CaCO3-introduced PVA2088. The PVA1799 layer was approximately 0.08 mm thick, and the PVA2088 layer was approximately 0.6 mm thick. 50 μL (33 mg / L) platelet solution was slowly added dropwise to the PVA bilayer film, and the film was incubated in a constant temperature incubator for 1.5 h. 50 μL of deionized water was slowly added dropwise to the platelet solution area of ​​the sample, and after wetting for 1 min, the deionized water was gently wiped off with absorbent paper. After standing for 48 h, the area of ​​the film with the platelet solution added was cut, platinum-coated, and SEM images were taken. Directly adding platelet solution to the membrane surface resulted in a denser fibrin network. Figure 19 This also indicates that the addition of calcium promotes the formation of fibrin network structure, providing conditions for subsequent platelet adsorption and activation, thereby promoting the coagulation process.

[0074] Example 14

[0075] 0.2% wt 100nm CaCO3 was added to a PVA2088 solution, and then a bilayer film was prepared using PVA1799 and PVA2088 with CaCO3 incorporation. The PVA1799 layer was approximately 0.08 mm thick, and the PVA2088 layer was approximately 0.6 mm thick. 50 μL (33 mg / L) platelet solution was slowly added dropwise to the PVA bilayer film, and the film was incubated in a constant temperature incubator for 1.5 h. 50 μL of deionized water was slowly added dropwise to the platelet solution area of ​​the sample, and after wetting for 1 min, the deionized water was gently wiped off with absorbent paper. After standing for 48 h, the area of ​​the film with the platelet solution added was cut, platinum-coated, and SEM images were taken. After directly adding platelet solution to the film surface, as the calcium carbonate content increased to 0.2 wt%, a thicker fibrin layer with smaller network pores was formed. Figure 20 ).

[0076] Example 15

[0077] A PVA2088 monolayer was prepared, and then PVA1799 was cast onto it to form a PVA bilayer film. The PVA1799 layer was approximately 0.08 mm thick, and the PVA2088 layer was approximately 0.6 mm thick. A 50 mg / L (human) protein solution was prepared and slightly inverted several times before use. The PVA bilayer film (10 × 10 mm) was placed in a 24-well plate with the PVA2088 side facing up. 50 μL of 50 mg / L protein solution was slowly added dropwise to the PVA bilayer film, and the plate was incubated in a constant temperature incubator for 1.5 h. 50 μL of deionized water was slowly added dropwise to the area where the 50 mg / L protein solution was added, and after wetting for 1 min, the deionized water was gently wiped off with absorbent paper. The plate was allowed to stand for 24 h. 50 μL (33 mg / L) platelet solution was slowly added dropwise to the area where the protein was incubated on the PVA bilayer film, and the plate was incubated in a constant temperature incubator for 1.5 h. Slowly add 50 μL of deionized water to the platelet solution inoculated area of ​​the sample, wetting for 1 min, then gently wipe away the deionized water with absorbent paper; after standing for 48 h, cut out the membrane from the area where the platelet solution was inoculated, platinum-coated, and then take SEM images. (After incubating proteins on the membrane surface, platelet solution was added...) Figure 21 Only a thin layer of fibrin network was formed in certain areas.

[0078] Example 16

[0079] Add 0.05% wt 100nm CaCO3 to the PVA2088 solution, then prepare a bilayer film using PVA1799 and CaCO3-introduced PVA2088, with the PVA1799 layer approximately 0.08 mm thick and the PVA2088 layer approximately 0.6 mm thick. Prepare a 50 mg / L (human) protein solution, gently inverting it several times before use. Place the PVA bilayer film (10 × 10 mm) in a 24-well plate with the PVA2088 side facing up. Slowly drop 50 μL of the 50 mg / L protein solution into the PVA bilayer film and incubate for 1.5 h in a constant temperature incubator. Slowly drop 50 μL of deionized water onto the 50 mg / L protein solution, wetting for 1 min, then gently wipe away the deionized water with absorbent paper and let stand for 24 h. 50 μL (33 mg / L) of platelet solution was slowly added dropwise to the protein incubation area of ​​the PVA bilayer membrane, and the sample was incubated in a constant temperature incubator for 1.5 h. 50 μL of deionized water was then slowly added dropwise to the platelet solution incubation area of ​​the sample, and after wetting for 1 min, the deionized water was gently wiped off with absorbent paper. After standing for 48 h, the membrane in the platelet solution incubation area was cut, platinum-coated, and SEM images were taken. In the sample where platelet solution was added after protein incubation on the membrane surface, a relatively thin fibrin network layer was formed, but the fibrin network was relatively dense. Figure 22 ).

[0080] Example 17

[0081] Add 0.1% wt 100nm CaCO3 to the PVA2088 solution, then prepare a bilayer film using PVA1799 and CaCO3-introduced PVA2088, with the PVA1799 layer approximately 0.08 mm thick and the PVA2088 layer approximately 0.6 mm thick. Prepare a 50 mg / L (human) protein solution, gently inverting it several times before use. Place the PVA bilayer film (10 × 10 mm) in a 24-well plate with the PVA2088 side facing up. Slowly drop 50 μL of the 50 mg / L protein solution into the PVA bilayer film and incubate for 1.5 h in a constant temperature incubator. Slowly drop 50 μL of deionized water onto the 50 mg / L protein solution, wetting for 1 min, then gently wipe away the deionized water with absorbent paper and let stand for 24 h. 50 μL (33 mg / L) of platelet solution was slowly added dropwise to the protein incubation area of ​​the PVA bilayer membrane, and the membrane was incubated in a constant temperature incubator for 1.5 h. 50 μL of deionized water was then slowly added dropwise to the platelet solution incubation area, and after wetting for 1 min, the deionized water was gently wiped off with absorbent paper. After standing for 48 h, the membrane from the platelet solution incubation area was cut, platinum-coated, and SEM images were taken. After incubating the protein on the membrane surface and then adding the platelet solution, as the calcium carbonate content increased to 0.1% wt, the thickness of the fibrin network significantly increased and became more dense. Figure 23 ).

[0082] Example 18

[0083] Add 0.2% wt 100nm CaCO3 to the PVA2088 solution, then prepare a bilayer film using PVA1799 and CaCO3-introduced PVA2088, with the PVA1799 layer approximately 0.08 mm thick and the PVA2088 layer approximately 0.6 mm thick. Prepare a 50 mg / L (human) protein solution, gently inverting it several times before use. Place the PVA bilayer film (10 × 10 mm) in a 24-well plate with the PVA2088 side facing up. Slowly drop 50 μL of 50 mg / L protein solution into the PVA bilayer film and incubate for 1.5 h in a constant temperature incubator. Slowly drop 50 μL of deionized water onto the 50 mg / L protein solution, wetting for 1 min, then gently wipe away the deionized water with absorbent paper and let stand for 24 h. 50 μL (33 mg / L) of platelet solution was slowly added dropwise to the protein incubation area of ​​a PVA bilayer membrane, and the membrane was incubated in a constant temperature incubator for 1.5 h. 50 μL of deionized water was then slowly added dropwise to the platelet solution incubation area, and after wetting for 1 min, the deionized water was gently wiped off with absorbent paper. After standing for 48 h, the membrane from the platelet solution incubation area was cut, platinum-coated, and SEM images were taken. After incubating the protein on the membrane surface and then adding the platelet solution, as the calcium carbonate content increased to 0.2% wt, a thicker fibrin network with smaller pores was formed. Figure 24 This also indicates that the addition of calcium promotes the formation of fibrin network structure to a certain extent, providing conditions for subsequent platelet adsorption and activation, thereby promoting the coagulation process.

[0084] The above description is merely a preferred embodiment of the present invention and is not intended to limit the scope of the invention. Various variations can be made to the above embodiments of the present invention. All simple and equivalent changes and modifications made in accordance with the claims and description of this application fall within the protection scope of the claims of this patent. All aspects not described in detail in this invention are conventional technical content.

Claims

1. A method for preparing a procoagulant hydrogel wound dressing, characterized in that, Includes the following steps: S1: Prepare a 5%~15% PVA2088 multi-bubble solution by adding PVA2088 to deionized water, and add calcium carbonate, wherein the concentration of calcium carbonate is 0.02~0.2 wt%; S2: Take an appropriate amount of PVA2088 multi-bubbling solution into a container, freeze and vacuum to remove internal bubbles, dry in an oven, and air dry at room temperature to obtain a PVA2088 hydrogel layer. S3: Dissolve PVA1799 in deionized water to prepare a 5%~10% PVA1799 solution; S4: Take an appropriate amount of PVA1799 solution and pour it onto the dried PVA2088 hydrogel layer obtained in step S2. Vacuum the solution, dry it in an oven, and air dry it at room temperature to finally obtain a hydrogel wound dressing composed of a PVA2088 hydrogel layer and a PVA1799 hydrogel layer.

2. The preparation method according to claim 1, characterized in that, Step S1 includes: adding a small amount of PVA2088 to deionized water to prepare a 0.5%~2% PVA2088 solution, then adding calcium carbonate, and then adding the remaining PVA2088 to mix and prepare a 5%~15% PVA2088 multi-bubble solution.

3. The preparation method according to claim 1, characterized in that, In step S1, the concentration of calcium carbonate in the PVA2088 multifoam solution is 0.02~0.05wt%.

4. The preparation method according to claim 1, characterized in that, In step S1, the calcium carbonate used has a particle size of 50~150nm.

5. The preparation method according to claim 1, characterized in that, Step S2 includes: drying in an oven at 50~60℃ for 4~6 hours, and then air-drying at room temperature for 48~72 hours.

6. The preparation method according to claim 1, characterized in that, Step S3 includes: adding PVA1799 to deionized water at 90~96℃ to prepare a 5%~10% PVA1799 solution.

7. The preparation method according to claim 1, characterized in that, Step S4 includes: evacuating the vacuum pump for 1-2 hours, then drying in a 50°C oven for 2-4 hours, and finally air-drying at room temperature for 24-48 hours.

8. A procoagulant hydrogel wound dressing prepared by the preparation method according to any one of claims 1 to 7, characterized in that, The bilayer hydrogel is a bilayer hydrogel composed of a PVA2088 hydrogel layer and a PVA1799 hydrogel layer, wherein, The PVA2088 hydrogel layer is made by dissolving calcium carbonate-doped PVA2088 in deionized water, with the calcium carbonate doping amount being 0.02~0.2% wt. The PVA1799 hydrogel layer is made by dissolving PVA1799 in deionized water.

9. The procoagulant hydrogel wound dressing according to claim 8, characterized in that, The thickness of the PVA2088 hydrogel layer is 0.55~0.65mm, and the thickness of the PVA1799 hydrogel layer is 0.06~0.1mm.

10. The application of the procoagulant hydrogel wound dressing according to claim 8 in the preparation of skin tissue repair and regeneration materials.

Citation Information

Patent Citations

  • Mussel-imitating double-network structure hydrogel material and application thereof in wound dressing

    CN116531556A

  • Fibrinogen bandages and methods

    WO2004010913A1